2015
DOI: 10.1038/srep16232
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 Regulates Cerebellar Development by Controlling Sonic Hedgehog-mediated Granule Cell Precursor Proliferation and Granule Cell Migration

Abstract: The Liver Kinase B1 (LKB1) gene plays crucial roles in cell differentiation, proliferation and the establishment of cell polarity. We created LKB1 conditional knockout mice (LKB1Atoh1 CKO) to investigate the function of LKB1 in cerebellar development. The LKB1Atoh1 CKO mice displayed motor dysfunction. In the LKB1Atoh1 CKO cerebellum, the overall structure had a larger volume and morelobules. LKB1 inactivationled to an increased proliferation of granule cell precursors (GCPs), aberrant granule cell migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 74 publications
2
19
1
1
Order By: Relevance
“…If Lkb1 were responsible for Hh signaling in GCPs, we would expect Lkb1 cko to be smaller than controls. However, consistent with the findings of others 26 , we noted that Lkb1 cko cerebella were considerably more foliated than littermate controls at adult stages (Figure 2A–B). Given that folia pattern and number were similar among Atoh1-cre; Lkb1 fl/+ , Lkb1 +/− , Lkb1 fl/+ , and Lkb1 fl/− littermates, the term “control” collectively refers to littermates of any of these genotypes.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…If Lkb1 were responsible for Hh signaling in GCPs, we would expect Lkb1 cko to be smaller than controls. However, consistent with the findings of others 26 , we noted that Lkb1 cko cerebella were considerably more foliated than littermate controls at adult stages (Figure 2A–B). Given that folia pattern and number were similar among Atoh1-cre; Lkb1 fl/+ , Lkb1 +/− , Lkb1 fl/+ , and Lkb1 fl/− littermates, the term “control” collectively refers to littermates of any of these genotypes.…”
Section: Resultssupporting
confidence: 93%
“…We find that GCP-specific loss of Lkb1 resulted in an expanded cerebellar cortex with increased foliation. In contrast to a recently published manuscript 26 , we find that increased foliation occurs without alteration of Hedgehog signaling or GCP proliferation. Neither the orientation of cell division nor mTOR signaling, a known downstream target of Lkb1, are responsible for changes in foliation.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Consistent with this finding, our results revealed that L. wallichii effectively downregulated UBE3A expression while retarding cell proliferation. Previous studies demonstrated that L. wallichii may change cell polarity (Amini et al, 2012), and this may affect UBE3A expression (Men et al, 2015). Thus, we speculated whether L. wallichii affects UBE3A expression by influencing the cell's polarity.…”
Section: Discussionmentioning
confidence: 94%